Autogenous tooth bone graft: Ingenious bone regeneration material - Chadalavada Sarala; Meghna Chauhan; P Sathyamurthy Sandhya; C H Dharmendra; Nirban Mitra (Wolters Kluwer Medknow Publications, 2018)
Tooth-derived bone graft material, which is proved to be rich in bone growth factors and bone morphogenic proteins (BMPs), have been becoming a practical substitute to bone grafting. It can also be used as a carrier for growth factors and stem cells as reported in many recent studies. Autogenous-tooth bone grafting technique is significant as this biomaterial has excellent bone regeneration capacity and also relatively non-existent chances of antigenicity, genetic diseases and disease transmission. In this article, a broad overview of the published findings with regard to the properties and uses of tooth-derived regenerative bone grafting is discussed.